Trends in PjBL to Improve Students' Scientific Creativity and Science Process Skills in Science Education (2010-2020): A Systematic Review - Lalu Syukran Muhsin; Abdul Syukur; Karnan Karnan (Balai Publikasi Indonesia, 2026)
The development of 21st-century skills requires science education to foster students’ scientific creativity and science process skills through innovative learning models. One instructional approach that has gained increasing attention is Project-Based Learning (PjBL). This study provides a systematic review of the trend of using Project-Based Learning (PjBL) Model in enhancing students' scientific creativity and science process skills during the period 2010-2020, using bibliometric analysis through the Publish or Perish 8 and VOSviewer tools. The results show a significant increase in publications focusing on PjBL, especially in the themes of STEM integration, critical thinking, problem solving, and collaborative learning. PjBL has been shown to not only enhance students' scientific creativity and science process skills, but also increase the interactivity and relevance of learning through the application of technology. Thematic cluster analysis shows a close relationship between educational innovation and cross-disciplinary collaboration in preparing students to face global challenges. From a practical perspective, the application of digital tools in PjBL is highly recommended, especially in distance learning and hybrid classes. This study suggests further exploration of more innovative evaluation methods to measure the impact of PjBL, and emphasizes the importance of implementing this approach to address the challenges of 21st-century education